Alacrity of Preschool Education Teachers to Work with Children in Inclusive Groups - Diatlenko, N.; Goncharenko, A.; Smolnykova, H.; Sabol, D.; Kocherga, O. (International Journal of Criminology and Sociology, 2021)
To make preschool inclusion successful and to have children gain the expected benefits, teachers need to be provided with functional teacher training programs that foster positive attitudes and provide them with a meaningful experience. The purpose of the study was to investigate the readiness of educators of preschool education institutions in Kyiv to work in inclusive classrooms. In the process of integration into the European community, Ukraine has focused on educational reforms, in particular, the creation of conditions for the introduction of inclusive education in educational institutions. The parameters of the research are taken into account, such as attitude to the idea of inclusion, possession of the necessary arsenal of pedagogical practices, understanding of barriers and ways to overcome them on the way to the organization of inclusive education. A structured questionnaire of preschool teachers attempts to reveal their attitudes towards inclusive education in general and to assess the conditions that promote or hinder the emergence of willingness and willingness to work in an inclusive group. The results of the study showed that a significant number of educators have a negative attitude to the idea of inclusion, believing that children should study in special groups or in special institutions (but not boarding schools). Educators name a number of barriers that prevent them from being positive about inclusive education, and underestimate their readiness for such work.